Analysing the predictors of financial stress and financial well-being among the bottom 40 percent (B40) households in Malaysia - Mansor, Maslina; Sabri, Mohamad Fazli; Mansur, Mustazar; Ithnin, Muslimah; Magli, Amirah Shazana; Husniyah, Abd Rahim; Mahdzan, Nurul Shahnaz; Othman, Mohd Amim; Zakaria, Roza Hazli; Mohd Satar, Nurulhuda; Janor, Hawati (Multidisciplinary Digital Publishing Institute, 2022)
This paper aims to analyse factors affecting financial stress among the Bottom 40 Percent (B40) group of Malaysian households, reflecting overall financial well-being. Data were collected through questionnaires from 1008 respondents across five major regions in Malaysia. The data were analysed using Exploratory Factor Analysis (EFA) and Partial Least Squares-Structural Equation Modelling (PLS-SEM). This study provides evidence that financial behaviour, financial vulnerability (debt and income), and locus of control (luck and self-confidence) significantly affect financial stress among B40 households. The results show a significantly positive relationship between financial stress with financial vulnerability (debt and income) and locus of control (self-confidence). On the contrary, financial behaviour and locus of control (luck) show a significant negative relationship with financial stress. The result also indicates that financial stress affects financial well-being. Overall, the findings indicate that policy-makers should invent more effective and substantial stimulus packages or other measures to reduce the financial burden on B40 households. The findings could eventually provide insights for future research to delve into the social impact of financial stress. This study also has established a valid and reliable instrument to measure financial stress involving B40 households in Malaysia that eventually reflects the financial well-being of this group of people.